The fall of the Templars - Young, Robyn 1975- (Plume, 2010)
Leaving the Christian empire in the East in ruins, Knight Templar Will Campbell returns to the West to discover that the Temple has forged an alliance with his enemy, King Edward of England, vowing to help the king wage war on Scotland, Will's homeland.